Right to Information act, 2005 (New Delhi, 2014)
The Right to Information Act 2005 is a legislation passed after years of people's struggle for securing a transparent, accountable and public participatory governance. The passing of this law by Parliament marks a notable milestone in the evolution of the Indian democracy.
Keywords: RTI-act-India